2016
DOI: 10.11152/mu.2013.2066.183.ays
|View full text |Cite
|
Sign up to set email alerts
|

Real-time sonoelastography of the patellar and quadriceps tendons: pattern description in profesional athletes and healthy volunteers.

Abstract: Aims: The comparison of elastographic features of quadriceps and patellar tendons in a group of professional athletes and healthy volunteers and the description of elasticity characteristics of these tendons. Material and methods: Thirtynine professional athletes (22 male, 17 female; mean age 18.5 years) and 35 healthy volunteers (21 male, 14 female; mean age 19 years) were included. They were divided into two groups by gender. Quadriceps tendon, patellar side of the patellar tendon, and tibial side of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 25 publications
4
52
2
1
Order By: Relevance
“…Porta et al 45 defined the normal appearance of patellar tendon at SE as a predominance of green pattern at proximal, middle, and distal portions. However the colour scale of sonographer ranged from red to green (red is defined as hard and green as soft tissue), and these results are in contrast with other Authors that found normal tendon to be harder and tendinopathic tendons to be softer 27,31,32 46 . Patellar tendon stiffness was found to be higher in male than female as well as in patients with lower BMI than obese individuals 47 .…”
Section: Patellar Ad Quadriceps Tendonscontrasting
confidence: 54%
See 1 more Smart Citation
“…Porta et al 45 defined the normal appearance of patellar tendon at SE as a predominance of green pattern at proximal, middle, and distal portions. However the colour scale of sonographer ranged from red to green (red is defined as hard and green as soft tissue), and these results are in contrast with other Authors that found normal tendon to be harder and tendinopathic tendons to be softer 27,31,32 46 . Patellar tendon stiffness was found to be higher in male than female as well as in patients with lower BMI than obese individuals 47 .…”
Section: Patellar Ad Quadriceps Tendonscontrasting
confidence: 54%
“…Only few studies were found dealing with quadriceps tendon. Healthy volunteers had prevalence of hard characteristics 46 . Teber et al 52 reported that normal quadriceps tendon patterns tended to change in case of chronic renal failure, in particular a substantial intratendinous softening occurred.…”
Section: Patellar Ad Quadriceps Tendonsmentioning
confidence: 99%
“…SE proved to be superior to B-mode ultrasound (sensitivity 99 %, specificity 78 %, accuracy 95 %) [318], underlining the ability of SE to detect pathology before the appearance of the B-mode ultrasound morphologic changes [319,320]. No differences between athletes and controls nor between the dominant and nondominant leg were found in SE evaluation of the patellar tendon [321]. With age, a significant decrease in shear wave velocity values was detected, with SWE having the capacity to detect aging tendons before morphologic abnormalities were observed on B-mode ultrasound [322,323].…”
Section: Tendonsmentioning
confidence: 88%
“…For conventional ultrasonographic and sonoelastographic examinations, dogs were positioned in lateral recumbency with the stifle in maximal passive flexion, to avoid the anisotropy of the fibrillar structures of the ligament. 40 The elastosonographic images were obtained by applying light rhythmic pressure with the probe. Only longitudinal sections were acquired, and the operators evaluated each patellar ligament twice.…”
Section: Methodsmentioning
confidence: 99%